Effects of Static Stretching With High-Intensity and Short-Duration or Low-Intensity and Long-Duration on Range of Motion and Muscle Stiffness - Fukaya, Taizan; Kiyono, Ryosuke; Sato, Shigeru; Yahata, Kaoru; Yasaka, Koki; Onuma, Remi; Nakamura, Masatoshi (Frontiers in Physiology, 2020)
This study investigated the effects of static stretching delivered with the same amount of total work but using two protocols – high-intensity and short-duration and low-intensity and long-duration – on range of motion (ROM) and muscle stiffness. A total of 18 healthy students participated in the study. They randomly performed high-intensity and short-duration (120% and 100 s) or low-intensity and long-duration (50% and 240 s) SS. Outcomes were assessed on ROM, passive torque at dorsiflexion ROM, and shear elastic modulus of the medial gastrocnemius before and after static stretching. The results showed that ROM at post-stretching increased significantly compared with pre-stretching in both groups. In addition, ROM at post in high-intensity and short-duration groups was significantly higher than that of low-intensity and long-duration. There were no significant interaction effects for passive torque at dorsiflexion ROM and shear elastic modulus, but there was a significant main effect of time. Our results suggest that a higher intensity of static stretching has greater effects on dorsiflexion ROM. However, variations in intensity and duration of static stretching with the same total work might not have a significant effect on shear elastic modulus.